Pengaruh waktu operasi dan daya mesin diesel dongfeng r175 berbahan bakar oli bekas terhadap emisi CO, CO2, HC, dan opasitas - A. Sasmita; Y. Yohanes; A.R. Widyanto (Dinamika Teknik Mesin, 2021)
The Production Laboratory of the Department of Mechanical Engineering, Riau University, has modified the diesel engine used as a used oil-fueled generator, but the problem is that the emission feasibility test has not been carried out. The purpose of this study was to analyze the relationship between the operating time and power of the diesel engine as a generator with the amount of emissions produced. This research was conducted by direct measurement of the emission produced by a diesel engine using a gas analyzer, by operating the diesel engine for 30 minutes and measuring emissions every 5 minutes. This study also varied the power load, starting at idle, 700 W, 1000 W, and a maximum power of 2000 W. The calorific value of used lubricant was tested using a bomb calorimeter are 50.445 kJ/kg. The results obtained are that the highest level of CO emission is 0.45%, the highest level of CO2 emission is 8.6%, the highest level of HC emission is 41 ppm, and the highest level of opacity is 70%.e